PERANAN KOMUNIKASI INTERPERSONAL ANTARA KARYAWAN DENGAN PELANGGAN DALAM PENANAMAN AKHLAK DI TOKO MA’HAD AL-ZAYTUN - Ridwan Daril Hakiki; Muhammad N. Abdurrazaq; Wiena Safitri; Elang Bakhrudin (STKIP Subang, 2024)
This research discusses the role of interpersonal communication between employees and customers in instilling morality at Ma’had Al-Zaytun Store. The research aims to understand how interpersonal communication plays a role in shaping good behavior among employees and customers and to identify factors that support or hinder this process. This study uses a qualitative method with interviews, observations, and document collection as data collection techniques. The results of the study show that good interpersonal communication between employees and customers plays an important role in instilling morality at Ma’had Al-Zaytun Store. Good and attentive interactions enable the instillation of desired moral values and maintain a positive organizational culture. Supporting factors include friendliness, patience, honesty, thinking skills, and an open organizational culture, while inhibiting factors include unclear information, cultural differences, unprofessional handling of conflicts, and lack of specific training. Keywords: Role, Interpersonal Communication, Moral Cultivation, Shop.